Preference for language of instruction of an English language learner with autism. (3rd May 2016) - Aguilar, Jeannie M.; White, Pamela J.; Fragale, Christina; Chan, Jeffrey Michael
Abstract: Objective : To use a preference assessment to identify the preferred language of instruction (English or Spanish) for a child with autism living in a Spanish-speaking home and receiving school services in English only. Methods : We used a concurrent chains method to evaluate the participant's preference for English or Spanish instruction. Colored microswitches represented English instruction, Spanish instruction and no instruction (control). Switch presses resulted in instruction and reinforcement in either English or Spanish, or no instruction and no reinforcement. After session 10, switches were reprogrammed to control for color bias. Results : The participant chose Spanish instruction most frequently. Conclusions : The participant preferred to receive instruction in Spanish. These data support previous research indicating the importance of child preference when individualizing educational programs for children with autism and that language of instruction is an important variable when working with children with autism who experience multiple languages across home and school.